Bio-legal analysis of the regulations on disaster risk management in Peru, in light of Laudato Si' - Gonzales-Montenegro, Katherinne Jhoana (2023)
It is important to contextualize the legal situation in Peru in relation to disaster risk management, which involves various professions and involves public and private entities. Faced the deficient and extremely poor capacity to manage rehabilitation and reconstruction processes in the face of disasters and emergencies in Peru was analyzed. In this sense, from a bio-legal approach, the national and international regulations regarding the National Disaster Risk Management System were analyzed; in turn under the guidelines of integral ecology and personal bioethics, the contribution of what it proposes is provided Laudato Si’, given the current challenges in defense of those affected, victims and the entire Peruvian population. The research had a qualitative approach of a social critical type and followed the research theme of Bio-legal, Biopolitical and Human Rights. As a result of this article, national and international regulations classified in the area of ​​disaster risk management were obtained and it is concluded that the implementation of this policy must be developed under the guidelines of Bio-legal and Personal Bioethics, in order to Legally respect the international instruments on Human Rights ratified by the Peruvian State, which are part of the block of conventionality and from which obligations in this matter are generated.